Tissue-specific Distribution and Dynamic Changes of 5-Hydroxymethylcytosine in Mammalian Genomes - Kinney, Shannon Morey (American Society for Biochemistry and Molecular Biology, 2011)
Cytosine residues in the vertebrate genome are enzymatically modified to 5-methylcytosine, which participates in transcriptional repression of genes during development and disease progression. 5-Methylcytosine can be further enzymatically modified to 5-hydroxymethylcytosine by the TET family of methylcytosine dioxygenases. Analysis of 5-methylcytosine and 5-hydroxymethylcytosine is confounded, as these modifications are indistinguishable by traditional sequencing methods even when supplemented by bisulfite conversion. Here we demonstrate a simple enzymatic approach that involves cloning, identification, and quantification of 5-hydroxymethylcytosine in various CCGG loci within murine and human genomes. 5-Hydroxymethylcytosine was prevalent in human and murine brain and heart genomic DNAs at several regions. The cultured cell lines NIH3T3 and HeLa both displayed very low or undetectable amounts of 5-hydroxymethylcytosine at the examined loci. Interestingly, 5-hydroxymethylcytosine levels in mouse embryonic stem cell DNA first increased then slowly decreased upon differentiation to embryoid bodies, whereas 5-methylcytosine levels increased gradually over time. Finally, using a quantitative PCR approach, we established that a portion of VANGL1 and EGFR gene body methylation in human tissue DNA samples is indeed hydroxymethylation.